Investigation of combustion and flame stabilization modes in a hydrogen fueled scramjet combustor. (9th November 2016) - Tian, Ye; Yang, Shunhua; Le, Jialing; Su, Tie; Yue, Maoxiong; Zhong, Fuyu; Tian, Xiaoqiang
Abstract: The combustion and flame stabilization modes in a hydrogen fueled scramjet combustor were investigated by experiments and numerical simulations in the present paper. The results were obtained with the inflow conditions of Mach number of 2.0, static temperature of 656.5 K and static pressure of 0.125 MPa, respectively. The equivalence ratio (ER) of hydrogen which was used as fuel changed from 0.04 to 0.30. Wall pressure measurement, schlieren, differential interferometry, high-speed framing of flame luminosity and OH-PLIF (planar laser-induced fluorescence) were introduced to characterize the combustion flow. Two typical combustion modes (scramjet mode and ramjet mode) could be attained by changing the ER of hydrogen. The combustion mode was scramjet mode when the ER of hydrogen was less than 0.23, while it was ramjet mode when the ER of hydrogen was greater than 0.23. When the combustion mode was scramjet mode, the flame stabilization mode was cavity shear layer stabilized combustion, and when the combustion mode was ramjet mode, the flame stabilization mode was combined cavity shear-layer/recirculation stabilized combustion. The flame was unstable and oscillated with the flow during the ramjet-mode operation. Highlights: Several non-intrusive approaches revealed interesting features about the reacting flowfield. Numerical results well matched the experimental results. Two combustion and flame stabilization modes were obtained and discussed.